(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Background: The waste generated during the delivery of health care services carries a high potential of hospital acquired infection. Biomedical Waste (BMW) collection and proper disposal has become a significant concern for both the medical and the general community2. In India approximately 0.33 million tons of hospital waste is generated yearly and in hospital settings 0.5-2.0 Kg of Biomedical waste is being generated per bed every day3. It is estimated that 10-25% of health care waste is hazardous, and if it is not properly segregated the entire 100% will be converted in to hazardous4. Objectives: This study was carried out to know the awareness and practice of Biomedical Waste management at tertiary care hospital. Methods: This cross sectional study was carried out on awareness and practice of Bio Medical Waste Management in a tertiary care hospital during 1st June 2018 to 31st August 2018 after obtaining permission from hospital authority. In this study total 120 health care professionals were included (60 doctors, 60 nurses, 60 laboratory staffs, 60 sanitary staff working in hospital). Conclusion: Knowledge regarding colour coding and risks of handling bio-medical waste was very poor especially among class-IV waste handlers hence there is a need to conduct training and retraining workshops on bio-medical waste management. Training of doctors on certain theoretical aspects of BMW, such as definition of BMW, BMW rules/legislation, and other such issues, is a must, as it is a teaching institution.